The Impact of Media Consumption on Voter Behavior in Serbia: Where Do Right-Wing Voters Get Their Political Information? - Ljubisic, Sofija; Bešić, Miloš (Political Life, 2026)
Media play a crucial role in shaping political attitudes and electoral behavior. This paper examines how daily media consumption, including television, online news portals, and social media platforms, affects the political behavior of four groups: voters of the ruling party, voters of the civic opposition, right-wing voters, and abstainers. Using logistic regression analysis, we assessed the impact of media consumption on the likelihood that voters will support particular parties or refrain from voting. The analysis includes demographic control variables such as age, level of education, urban or rural residence, and regional differences. Logistic regression was employed to explain the predictors of different types of media consumption on voting behavior. The dependent variables represent the probability of voting for each of the four groups, while the independent variables include demographic factors and media consumption.The results indicate that media consumption significantly influences voter behavior, with television and online news portals having a stronger effect compared to social media. The ruling party benefits most from traditional media (television), while right-wing parties gain substantial support through online portals. Social media platforms show mixed effects, with certain platforms such as Facebook and Instagram emerging as spaces of support for right-wing voters.
Keywords: media consumption, electoral behavior, logistic regression, political parties.